(untitled) - Pym, Barbara (New York, 1978)
Excellent Women is one of Barbara Pym’s richest and most amusing high comedies. Mildred Lathbury is a clergyman’s daughter and a mild-mannered spinster in 1950s England. She is one of those "excellent women," the smart, supportive, repressed women who men take for granted. As Mildred gets embroiled in the lives of her new neighbors—anthropologist Helena Napier and her handsome, dashing husband, Rocky, and Julian Malory, the vicar next door—the novel presents a series of snapshots of human life as actually, and pluckily, lived in a vanishing world of manners and repressed desires.
Keywords: Single women,Người đàn bà đơn độc; Fiction,Tiểu thuyết